Glucagon‐like peptide‐1 agonists for treatment of hidradenitis suppurativa. (1st September 2017) - Emtestam, L.; Sartorius, K.
Abstract: Linked Article: Jennings et al . Br J Dermatol 2017; 177 :858–859 .